2022
DOI: 10.25259/jgoh_17_2021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity and dental caries experience in patients attending Tagore Dental College, Chennai, India: A cross-sectional survey

Abstract: Objectives: This study aims to assess the relationship between body mass index (BMI) and dental caries experience among the patients attending the outpatient department of Tagore Dental College, Chennai, India. Materials and Methods: A cross-sectional study with a convenient sampling technique was employed in the outpatient department of Tagore Dental College, Chennai, India. Obesity was recorded by measuring the BMI. Dental caries experience was recorded using the World Health Organization’s recommended “de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…( 22) Patel and colleagues showed that the developing of periodontitis was higher in patients with blood group B and O and those who are Rh positive . (23) However, Francis et al, reported a no significant relation was found between ABO , Rh factor and periodontal diseases (24). In 1 -1 1977 to 2016, using ABO blood groups, dental health, risk factors, gingivitis, periodontitis and Rhesus factor as searching terms and he found a difference according to geographical diversity.…”
Section: Abo and Rh In Periodontal Diseasesmentioning
confidence: 99%
“…( 22) Patel and colleagues showed that the developing of periodontitis was higher in patients with blood group B and O and those who are Rh positive . (23) However, Francis et al, reported a no significant relation was found between ABO , Rh factor and periodontal diseases (24). In 1 -1 1977 to 2016, using ABO blood groups, dental health, risk factors, gingivitis, periodontitis and Rhesus factor as searching terms and he found a difference according to geographical diversity.…”
Section: Abo and Rh In Periodontal Diseasesmentioning
confidence: 99%